PP70 Knowledge Brokers or Policy Entrepreneurs? Strategies to Influence the Policy Process. (10th September 2013) - Oliver, K; Money, A; Vocht, F de
Abstract : Background: Understanding the impact and process of evidence-use in policy has been a major focus for researchers in recent years. Researchers often focus on (a) how to increase uptake of research, (b) validating models of knowledge transfer and (c) advocating for the use of knowledge brokers. Several 'job descriptions' for knowledge brokers have been published. However, the influence and impact of knowledge brokers is unclear. Policy actors who are known to be influential can also be characterised in terms of daily activities. This study aims to describe the activities of powerful and influential actors and compare them with knowledge brokerage frameworks from the literature. Methods: A policy community in a large UK conurbation was defined as 'involved in delivering, developing or implementing public health policy', and included regional and national actors. Policy actors' accounts of the policy process (including evidence use, policy processes and policy networks) were gathered through 23 semi-structured interviews and over 18 hours of observations of NHS and local authority meetings, both public and private. Data were analysed using framework analysis. Results: Knowledge brokerage roles were identified as part of the policy process, but were played by policy makers already in the policy community, rather than researchers and academics. Knowledge brokerage frameworks describe the involvement of policy makers in the research process, but descriptions of other activities involved in the policy process showed that knowledge brokerage strategies formed a small part of a much wider spectrum of policy-influencing strategies; controlling policy organisations, controlling policy content, controlling decision-makers and using relationships. These activities take place over long time periods, and over a range of policy areas, questioning the utility of constructions such as "public health policy" for analysing evidence-use and policy processes. Discussion: Knowledge brokerage is often presented as an intervention to increase research uptake, to be carried out by researchers. We show that the activities described are carried out by actors within the policy environment, questioning the usefulness of such approaches. Knowledge brokerage forms a small part of a spectrum of policy-influencing strategies employed by policy actors, who operate over a longer time-span and a wider range of policies than previously acknowledged. Providing empirical descriptions of the activities of policy actors provides insight into both how to influence policy, and a framework to understand the policy process itself.